Artificial intelligence and human person - Nicola Rotundo (Cuadernos de Teología - Universidad Católica del Norte)
This article examines the controversy of the so-called artificial intelligence with a specific regard to its use in medical, biomedical and industrial fields. The purpose of this present study is to provide a moral and theological perspective on the matter drawing upon the Western epistemological tradition and incorporating the difference between consciousness and conscience: being inspired by Prof. Schinella’s analysis about the foundation of the moral action of the faithful based on the relation between charity and law and, considering the Christian concept of conscience as a practical last judgement of the person called to do good and to avoid evil, we have investigated the role of conscience as true inviolable sanctuary, in Saint Paul II words. Whilst it is accurate to state that clinical benefits derive from the use of artificial intelligence concerning diagnosis, certain criticisms have been articulated, even by those who were first its advocates. Including evidence from the Christian Tradition and the latest studies of neuroscience, this study demonstrates that the development of the artificial intelligence amplifies the ethical implications.